2022
DOI: 10.3390/polym14030509
|View full text |Cite
|
Sign up to set email alerts
|

ABS/Silicon Dioxide Micro Particulate Composite from 3D Printing Polymeric Waste

Abstract: In this paper, Acrylonitrile-Butadiene-Styrene matrix composites reinforced with Nano-silica dioxide particles were examined and prepared to study their mechanical properties. The composite sheets were pre-prepared using the hot extrusion process. Due to its wide characteristics, silica dioxide additions can strengthen the usability and mechanical features of composite thermoplastics and polymers. Furthermore, introducing silica dioxide as a filler in various attributes can help to maintain the smooth flow of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 107 publications
0
10
0
Order By: Relevance
“…Figure 15 presents the Ultimate Strength of the produced samples. It has been shown that the ultimate strength of the CF/PLA bends increased with the increase of the CF contents, with an increase from 7% to 28% for the CFRP at 10% and 20% contents, respectively, in comparison to the recycled PLA [ 95 ]. On the other hand, it is shown that the CFRP/PLA ultimate strength increased slightly concerning the recycled PLA, but it has a lower level than the CF/PLA blends, which is ascribed to the presence of the expired impregnated epoxy, as clarified before.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 15 presents the Ultimate Strength of the produced samples. It has been shown that the ultimate strength of the CF/PLA bends increased with the increase of the CF contents, with an increase from 7% to 28% for the CFRP at 10% and 20% contents, respectively, in comparison to the recycled PLA [ 95 ]. On the other hand, it is shown that the CFRP/PLA ultimate strength increased slightly concerning the recycled PLA, but it has a lower level than the CF/PLA blends, which is ascribed to the presence of the expired impregnated epoxy, as clarified before.…”
Section: Resultsmentioning
confidence: 99%
“…The trends of the ductility of the composite blends, i.e., the strains recorded at the point of failure during the tensile testing procedure, have been graphically plotted in Figure 16 . It has been observed that the recycled PLA ductility has a higher strain (6.01%) at the failure point in comparison with the commercial PLA filament (5.2%), with an increase of around 15% in ductility due to the degradation of the recycled properties during the recycling process [ 95 ]. Moreover, clear evidence illustrates that the CF/PLA composite suffered from a remarkable drop in ductility ranging from 43% to 30% for the 10% and the 20% CF reinforcement, respectively, which is attributed to the impact of the carbon fiber reinforcement.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the use of 3D printing technology for the preparation of antimicrobial polymeric composites could enhance their characteristics and performance through the consistent extrusion process. Therefore, this technology may be helpful for further investigations and applications in the biomedical, food, space, and textile fields, as well as other science and technology applications like recycling of waste materials [ 112 , 113 , 114 ] and implementing nanotechnology for better performance [ 115 ]…”
Section: Discussionmentioning
confidence: 99%
“…Numerous qualities of the copolymer composed of acrylonitrile, butadiene, and styrene include low weight, ease of formability, resistance to abrasion [20]. In the manufacture of car components, sports equipment, and toys such as Lego blocks often rely on ABS as the material used [21] and listed in Table A4 (see Appendices).…”
Section: Methodsmentioning
confidence: 99%